2011
DOI: 10.7196/samj.4469
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of safe endotracheal tube cuff pressures in emergency care - time for change?

Abstract: To the Editor: Endotracheal intubation is performed in the prehospital and emergency department (ED) environments by advanced life support (ALS) paramedics and emergency doctors. Cuffed endotracheal tubes (ETTs) are used in adults and more recently in children 1 to ensure that the airway is protected, and to prevent air leakage between the wall of the trachea and the ETT during positivepressure ventilation. Cuffs are typically high volume, low pressure in their design and have a safe working pressure of <30 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…[ 8 ] Digital balloon palpation corresponds poorly with the measured endotracheal cuff pressure, and anesthetist experience corresponds poorly with measured cuff pressures. [ 8 10 11 12 ] The instrumental measurement and adjustment of cuff pressure resulted in a significantly lower incidence of postprocedural sore throat, hoarseness, and blood-stained expectorant. [ 12 ] The pressure exerted on the tracheal wall depends on the compliance of the trachea and the pressure measured at the pilot balloon of an ETT cuff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] Digital balloon palpation corresponds poorly with the measured endotracheal cuff pressure, and anesthetist experience corresponds poorly with measured cuff pressures. [ 8 10 11 12 ] The instrumental measurement and adjustment of cuff pressure resulted in a significantly lower incidence of postprocedural sore throat, hoarseness, and blood-stained expectorant. [ 12 ] The pressure exerted on the tracheal wall depends on the compliance of the trachea and the pressure measured at the pilot balloon of an ETT cuff.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 10 11 12 ] The instrumental measurement and adjustment of cuff pressure resulted in a significantly lower incidence of postprocedural sore throat, hoarseness, and blood-stained expectorant. [ 12 ] The pressure exerted on the tracheal wall depends on the compliance of the trachea and the pressure measured at the pilot balloon of an ETT cuff. ETT cuff pressure can be considered as a good estimate of the pressure exerted on the tracheal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that palpation of the pilot-balloon has no correlation with the actual pressure in the cuff and the sensitivity is around 50% in most studies. 10 , 15 , 23 , 26 While this is a well-known fact, few prehospital, emergency centre or anaesthesia services use cuff-manometry as the standard of care. Studies in paramedic systems have consistently demonstrated cuff over-inflation in services not using routine cuff-pressure monitoring and part of the challenge lies in the varied recommended range of pressures that are considered acceptable (between 20 and 45 cm H 2 O).…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Stein et al highlighted the inability of advanced life support paramedics and emergency department doctors in Johannesburg to accurately estimate safe ETT cuff pressures using the palpation technique alone. 11 Multiple studies have found serious complications following longer duration of intubation, with the incidence and severity increasing proportionally to the duration. Cuff pressure itself may also change over time.…”
Section: Discussionmentioning
confidence: 99%